MEASUREMENT OF WORKLOAD WITH WORK SAMPLING AND WORKLOAD ANALYSIS IN PT. VUB - Maulana, Muhammad Rifqi; Putra, Boy Isma (Universitas Nusantara PGRI Kediri, 2022)
PT. Varia Usaha Beton As a company engaged in the downstream cement product industry, work productivity is one of the main components in determining the success of the implementation of a production, for the paving production section in this December PT. Varia Usaha Beton produces as many as 67482 paving, with product defects as many as 1290 paving and for the number of paving passing the test as many as 66192, so the purpose of this research is to maximize production targets and can find out the standard time required by workers in completing work in the production section. this time the researcher uses work sampling method, work sampling is a technique to conduct a large number of observations on the work activities of workers. Observation of work activity for an interval of time taken at random on one or more workers and then recording whether the worker is in work or unemployed. Workload analysis or workload is an effort that must be expended by someone to meet the demands of the job. The results from the observation of the data above obtained a productive percentage value of 0.73, and a non-productive percentage value of 0.27, a delay ratio of 0.36 performance level of 73%, the number of productive minutes is 11096 so, it can be determined that one product can be completed in 19.81 minutes, p is 0.73, the upper control limit is 0.89, the lower control limit is 0.57, with the workload is 93.74%, therefore it can be said to be good because it is not more than 100%.